EDRMS Users' Information-Seeking Behaviour: Managerial and Training Challenges For Records Managers - Singh, Pauline; Klobas, J.; Anderson, K. (Records Management Association of Australia RMAA, 2008)
Drawing on findings of their field study on the information-seeking behaviour of 40 Electronic Document & Records Management System (EDRMS) users in 4 organisations using different EDRMS – published in the last 3 issues of IQ – the authors here set out to alert records managers to the managerial and training challenges they need to consider to better serve their EDRMS users.